2008
DOI: 10.2105/ajph.2007.110767
|View full text |Cite
|
Sign up to set email alerts
|

SEXINFO: A Sexual Health Text Messaging Service for San Francisco Youth

Abstract: In response to rising gonorrhea rates among African American youth in San Francisco, Calif, Internet Sexuality Information Services, Inc, in partnership with the San Francisco Department of Public Health, developed SEXINFO, a sexual health text messaging service. SEXINFO is an information and referral service that can be accessed by texting "SEXINFO" to a 5-digit number from any wireless phone. A consortium of community organizations, religious groups, and health agencies assisted with identifying culturally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(164 citation statements)
references
References 2 publications
4
159
0
Order By: Relevance
“…The m4RH system builds on earlier programs that used SMS to reach targeted audiences with health information [18,19]. Mobile for Reproductive Health is the first program to focus on contraception in Sub-Saharan Africa; the automated and interactive features of the program and the searchable database of clinic locations add to its innovative nature.…”
Section: Discussionmentioning
confidence: 99%
“…The m4RH system builds on earlier programs that used SMS to reach targeted audiences with health information [18,19]. Mobile for Reproductive Health is the first program to focus on contraception in Sub-Saharan Africa; the automated and interactive features of the program and the searchable database of clinic locations add to its innovative nature.…”
Section: Discussionmentioning
confidence: 99%
“…24 mHealth as a field within the health system thrives on multi-sector partnerships especially in program design and implementation. 57 mHealth in ASRH rides on existing health interventions (e.g. health education), working to bridge existing gaps to improve its effect and coverage as shown in Figure 4.…”
Section: Use Of Mhealth In Asrh Promotionmentioning
confidence: 99%
“…64,65 The effect of SMS on sexual healthcare seeking behaviour was evaluated among young people in the United States using the SEXINFO free SRH-SMS information and referral service. 57 The service was instituted in response to the rising gonorrhoea rates among African-American young people in San Francisco. The study reported a significant increase in STI testing and use of clinical services.…”
Section: Figure 4: Mhealth In Asrh As a Catalyst For Effective Coveramentioning
confidence: 99%
See 2 more Smart Citations